Can Cognitive Remediation in Groups Prevent Relapses?: Results of a 1-Year Follow-up Randomized Controlled Trial. Issue 5 (May 2020) - Mueller, Daniel R.; Khalesi, Zahra; Roder, Volker
Abstract : Abstract: International guidelines define relapse prevention for schizophrenia patients as a key therapeutic aim. However, approximately 80% to 90% of schizophrenia patients experience further symptom exacerbation after the first episode. The purpose of this study was to investigate whether group integrated neurocognitive therapy (INT), a cognitive remediation approach, reduces relapse rates in schizophrenia outpatients. INT was compared with treatment as usual (TAU) in a randomized controlled trial. Fifty-eight stabilized outpatients participated in the study with 32 allocated to the INT group and 26 to the TAU group. A test battery was used at baseline, posttreatment at 15 weeks, and a 1-year follow-up. Relapse rates were significantly lower in the INT condition compared with TAU during therapy as well as at follow-up. The relapse rate after therapy was associated with significant reductions in negative and general symptoms, improvements in functional outcome, and overall cognition. Out of these variables, negative symptoms were identified to show the strongest association with relapses after therapy. The primary outcome of this study suggests that INT can prevent relapses in schizophrenia outpatients.